Upaya Penyeimbangan Kapasitas Stasiun Kerja Dengan Pendekatan Theory Of Constraint - Wahyuni, Dini; Syahputri, Khalida; Mangunsong, Evalina (Media Teknika, 2016)
This research was conducted in fishmeal processing companies in North Sumatera. The production process are sorting, washing, heating, pressing, drying, milling and packaging. Heating, pressing, and drying has the smallest capacity work station which is 1 ton per hour, while the washing station is 4 ton per hour, lead to bottleneck. Stop Watch Time study used to measure working elements’ cycle time in each work station during the 10 days of observation. Observation data tested by uniformity and adequacy test before determining standard time of working process. Demand for a year later is predicted using cyclical method so that capacity requirement can be obtained from that prediction and standard time of process. Theory of Constraint (TOC) is used to solve the bottleneck. Research showed that data measured are uniform and adequate; while constraint are found at the heating, pressing, and drying work station due to smaller capacity. That constraints can be solved by using five steps of TOC which obtained four alternative solutions, which is work load adjustment, overtime, addition of shifts or addition of machines. Alternatives for work load adjustment and addition of machines are not feasible after calculating them. Feasible alternatives are overtime and addition of shifts, which lead to cost consequences between them. Recommendation from this research is addition of shifts from 2 to 3 shifts per day to increased capacity for each heating, pressing and drying stations because they have the lower cost consequences.